Use of plants and animals by the riverine population from Rio Vermelho Community, central western Brazil - Valadares, Lohan Claudio Abreu; Pasa, Maria Corette (Interações, 2016)
This study approached Rio Vermelho community, in the state of Mato Grosso. This type of community is important for supplying the cities with fruits, vegetables and products made from animal’s extract. Data obtained shows natural resources are more related to a source of income than self-consumption and the perception of nature in a sense of awe and beauty, not considering important organisms that indirectly benefi ts or harms their crops and breeding.